"Fine ... I'll do it myself": Lessons from self-employment grants in a long recession period - Stjepan Srhoj; Ivan Zilic (IZA Journal of Labor Policy, 2021)
This paper evaluates the effect of a self-employment grant scheme for unemployed individuals-designed to ease the first 12 months of business operation-on firm growth, survival, and labor market reintegration in Croatia in the 2010-2017 period. Grants offered a moderate amount of finances (up to 50% of average annual gross salary) and absorbed only 5% of funds allocated to active labor market policies (ALMPs), but accounted for 10% of new firms opened throughout the years. We contribute to the literature on self-employment grants with several novel findings. Exploiting the longitudinal structure of the unemployment episodes dataset, we find that individuals who finish their spell with a grant have a significantly lower probability of returning to unemployment. The policy is particularly effective for individuals who would have otherwise had labor market opportunities (men, more educated, prime-age workers, previously employed), individuals who became unemployed after inactivity and lost their job due to a firm's closure-which demonstrates that self-employment subsidies can be effective in ameliorating unemployment. However, the policy was not effective for longer unemployed individuals. At the firm level, we find descriptive evidence that limited liability firms opened via a grant have lower growth potential and worse survival profile, while unlimited liability firms-even though a sizable portion of them closes after a required 12-month grant period-have a more favorable survival profile. Finally, we also find that the effectiveness of these grants has increased throughout the years, indicating toward the direction of institutional learning.
Keywords: J68; M13; H25; H43; 330; self-employment grant; evaluation; unemployment; firm performance